A versatilidade fotocatalítica dos óxidos de nióbio: semicondutores estratégicos para a síntese ou degradação de compostos na região do UV-Vis - José Balena Gabriel Filho (2023)
Niobium oxide-based semiconductors have attracted attention in the field of heterogeneous photocatalysis due to their excellent ability to promote redox transformations and synthesis versatility. In this theses, selective processes under UV or Visible radiation, never performed before with niobium photocatalysts, were investigated. In one of the cases it was discovered that commercial niobic acid (called HY-340), produced by Companhia Brasileira de Metalurgia e Mineração (CBMM), has a special ability to reduce levulinic acid (LA) to γ-valerolactone (GVL), a high value-added lignocellulosic biomass molecule. This conversion was observed in the absence of co-catalysts (noble metals) or additives, only using ethanol as a hole scavenger and UV radiation. In long reaction times, it was observed that the LA by-products initially detected were also transformed into GVL, after 72 consecutive hours of reaction the selectivity reached 44.7%, a formidable result using an amorphous solid as photocatalyst. In order to investigate the improvement in LA reduction through structural modifications, niobic acid was thermally treated at temperatures of 200, 400 and 600 °C. The best performance was achieved for the material synthesized at 600 °C, called H3. Oxygen vacancies were created in this niobium oxide just by changing the static air atmosphere to a H2 flow (10% in N2), these defects increased the conversion from 36.4% to 43.5% without losing selectivity. The aforementioned studies about LA conversion were the pioneers on the use of pure niobium oxides for the selective reduction of organic compounds. To highlight the versatility of niobium in social concern technological applications, a photoactive fabric based on polycaprolactone (biodegradable polymer) containing iron niobate particles was designed for the degradation of organophosphates, in this case the acutely toxic Methyl Paraoxon was used as a model. The results showed that in 48 hours of exposure to light, the fabric eliminates 94.5% of Methyl Paraoxon, converting it even into phosphoric acid, less toxic phosphorus compound. Combining the technological use of Nb to add value to lignocellulosic biomass derivatives and the destruction of organophosphate compounds is quite importance for Brazil, since the country has the largest reserves of niobium in the world, as well as it is prominent in the world market of agricultural feedstock and consequently the lignocellulosic biomass.